3 d : die dritte dimension. - Pappermann, Mirela; Galerie haas & Fuchs, Berlin (Berlin : Galerie Haas & Fuchs Berlin, 2005)
Arp, Hans (Jean) ; Chillida, Eduardo ; Christian, Abraham David ; Fontana, Lucio ; Graubner, Gotthard ; Grünfeld, Thomas ; Heerich, Erwin ; Kiefer, Anselm ; Knoebel, Imi ; Locher, Thomas ; Paladino, Mimmo ; Paolozzi, Eduardo ; Sachs, Tom ; Schumacher, Emil ; Schwitters, Kurt ; Soto, Jesus Rafael ; Uecker, Günther
Exhibition in Galerie Michael Haas in Berlin, 18.03.2005 - 30.04.2005
Duits
boek